Gender Representation of Flouting Maxim in Classroom Interaction Videos on Youtube - Oktazsya Marjelina Lorenza; Safnil Arsyad; Syafryadin Syafryadin (Universitas Galuh, 2023)
This article analyzes the flouting types of maxim in classroom interaction videos on YouTube. The aims of this study are to find out the flouting types of maxim and also the gender representation of it. Descriptive qualitative method was used. The corpus of the study were 10 classroom interaction videos that were taken from YouTube. Grice’s theory was used to find and analyze the flouting types of maxim found in the video, those are; maxim of quality, quantity, relevance, and manner. The result showed that those four types of flouting maxim were found in the classroom interaction videos on YouTube. The highest flouting maxims found were maxim of quantity, relevance and manner and the least one is maxim of quality. This is probably because the speaker wants to build trust and cheer the hearer. The findings of the second research question shows that male was the most dominant gender flouting the maxims. Based on the results and limitation of the study, it is recommended for further research to take the data directly to schools to compare videos taken from YouTube and those taken directly from schools.